Molecular enneanuclear CuII phosphates containing planar hexanuclear and trinuclear sub-units: syntheses, structures, and magnetism. Issue 8 (5th February 2020) - Santra, Biswajit; Kalita, Pankaj; Chandra, Shubhadeep; Mandal, Debdeep; Kumar, Vierandra; Narayanan, Ramakirushnan Surya; Dey, Atanu; Chrysochos, Nicolas; Huch, Volker; Biswas, Sourav; Ghoshal, Debajyoti; Sañudo, E. Carolina; et al.
Abstract : Highly symmetric enneanuclear copper(ii ) phosphates comprising of a hexanuclear and a trinuclear motif are described. Abstract : Highly symmetric enneanuclear copper(ii ) phosphates [Cu9 (Pz)6 (μ-OH)3 (μ3 -OH)(ArOPO3 )4 (DMF)3 ] (PzH = pyrazole, Ar = 2, 6-(CHPh2 )2 -4-R-C6 H2 ; R = Me, 2 MeAr ; Et, 2 EtAr ; iPr, 2 iPrAr ; and Ar = 2, 6-iPr2 C6 H3, 2 Dip ) comprising nine copper(ii ) centers and pyrazole, hydroxide and DMF as ancillary ligands were synthesized by a reaction involving the arylphosphate monoester, 1, copper(i )chloride, pyrazole, and triethylamine in a 4 : 9 : 6 : 14 ratio. All four complexes were characterized by single crystal structural analysis. The complexes contain two distinct structural motifs within the multinuclear copper scaffold: a hexanuclear unit and a trinuclear unit. In the latter, the three Cu(ii ) centres are bridged by a μ3 -OH. Each pair of Cu(ii ) centers in the trinuclear unit are bridged by a pyrazole ligand. The hexanuclear unit is made up of three dinuclear Cu(ii ) motifs where the two Cu(ii ) centres are bridged by an –OH and a pyrazole ligand. The three dinuclear units are connected to each other by phosphate ligands. The latter also aid the fusion of the trinuclear and the hexanuclear motifs. Magnetic studies reveal a strong antiferromagnetic exchange between the Cu(ii ) centres of the dinuclear units in the hexanuclear part and a strong spin frustration in the trinuclear part leading to a degenerate ground state.